1992
DOI: 10.1161/01.str.23.5.686
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cerebral hypoperfusion compared among demented and nondemented patients with stroke.

Abstract: Background and Purpose:No reports are available that compare local cerebral perfusion among groups of patients suffering from multiple cerebral infarctions with and without cognitive impairments. The present study was designed to correlate changes in regional cerebral perfusion that may lead to dementia among patients with multiple cerebral infarctions by comparing measurements of local cerebral blood flow.Methods: Local perfusion was measured using xenon-contrasted computed tomographic scanning among two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…The location of white matter changes may also influence cognitive functions: amongst patients with lacunes, those who have dementia have more white matter lesions in the frontal lobes and their severity correlates with the cognitive decline [33,53]. Demented patients with multiple cerebral infarcts have lower perfusion rates of frontal and temporal cortical regions [54]: leukoaraiosis causing cortical disconnection is held responsible. It is wise to consider patients with white matter changes as prone to develop neuropsychological deficits, although several of them could probably remain free of any clinical abnormality [50].…”
Section: White Matter Changes May Contribute To Cognitive Declinementioning
confidence: 99%
“…The location of white matter changes may also influence cognitive functions: amongst patients with lacunes, those who have dementia have more white matter lesions in the frontal lobes and their severity correlates with the cognitive decline [33,53]. Demented patients with multiple cerebral infarcts have lower perfusion rates of frontal and temporal cortical regions [54]: leukoaraiosis causing cortical disconnection is held responsible. It is wise to consider patients with white matter changes as prone to develop neuropsychological deficits, although several of them could probably remain free of any clinical abnormality [50].…”
Section: White Matter Changes May Contribute To Cognitive Declinementioning
confidence: 99%
“…The location of white matter changes might also influence cognitive functions: patients with lacunes and dementia have more white matter lesions in the frontal lobes and their severity correlates with the cognitive decline [130,131]. Lower perfusion rates of frontal and temporal cortical regions are seen in demented patients with multiple cerebral infarcts [132]: underlying white matter changes causing cortical disconnection were held responsible.…”
Section: Multifactorial Origin Of Vadmentioning
confidence: 99%
“…(1992), in a CT and PET study of patients with leukoaraiosis, reported that frontal leukoaraiosis contributed to dementia and was considered of ischemic origin, while parietal and occipital leukoaraiosis was considered to be due to Wallerian degeneration. Correlations of leukoaraiosis with cerebral hypoperfusion have been reported (De Cristofaro et al, 1990;Kawamura et al, 1991 a, b;Terayama et al, 1992;Yao etal., 1990). Scheltens etal.…”
Section: Differentiation Of Primary Degenerative and Vascular Dementiamentioning
confidence: 94%